A Novel Photo‐thermochemical Approach for Enhanced Carbon Dioxide Reforming of Methane. Issue 5 (29th January 2018) - Pan, Fuping; Xiang, Xianmei; Deng, Wei; Zhao, Huilei; Feng, Xuhui; Li, Ying
Abstract: We report a new approach for photo‐thermochemical CO2 (dry) reforming of methane (PTC‐DRM) to produce syngas by using concentrated sunlight as the energy input. A unique catalyst, Pt‐supported Si‐modified CeO2, was designed for this novel PTC‐DRM reaction by integrating photocatalytic and thermocatalytic effects, for which Pt was the thermocatalytic DRM catalyst and co‐catalyst for photocatalysis, CeO2 was the DRM support and semiconductor photocatalyst, and Si was the promoter and stabilizer. Under irradiation of the equivalent of 30 suns at 600 °C in 30 h, the production rates of H2 and CO reached stable levels of 90 and 154 mmol g −1 h −1, respectively, which were five and two times higher than those obtained in the dark at the same temperature. The significantly enhanced catalytic performance and stability under solar irradiation, resulting from synergy between the photocatalytic and thermocatalytic effects, demonstrates the feasibility of a new direction in low‐carbon fuel production from sunlight. Abstract : Two‐in‐one catalysis : A new approach for photo‐thermochemical CO2 (dry) reforming of methane (PTC‐DRM) to produce syngas is proposed by using concentrated sunlight as the energy input and Pt‐supported Si‐modified CeO2 as the catalyst. PTC‐DRM is much more efficient than thermo‐DRM in both activity and stability owing to synergy between the photocatalytic and thermocatalytic effects. CB= conduction band, VB=valence band.